2022
DOI: 10.1002/emp2.12763
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening the stroke chain of survival in community emergency departments

Abstract: Strengthening the stroke chain of survival in community emergency departmentsIn this issue of JACEP Open, Zachrison et al 1 of the American College of Emergency Physicians Emergency Quality Network, an educational and quality improvement collaborative of emergency departments (EDs) across the United States, describe the diagnostic and treatment capabilities of community EDs for acute stroke. The study population in Zachrison et al primarily consisted of community EDs without a stroke center certification, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Acute stroke care is an emergency that is conceptualized as a stroke survival chain occurring between stroke onset and appropriate disposition of the acute stroke patient receiving reperfusion therapy, and includes the eight steps of acute stroke recognition, diagnosis, and treatment ( 6 , 16 ). Delays in any step can lead to delays in overall treatment and may even make the patient ineligible for certain reperfusion therapies ( 16 ). Especially in geographic areas with limited stroke centers, PHPs can be reconceptualized as the backbone of the stroke survival chain in some low- and middle-income countries or regions ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Acute stroke care is an emergency that is conceptualized as a stroke survival chain occurring between stroke onset and appropriate disposition of the acute stroke patient receiving reperfusion therapy, and includes the eight steps of acute stroke recognition, diagnosis, and treatment ( 6 , 16 ). Delays in any step can lead to delays in overall treatment and may even make the patient ineligible for certain reperfusion therapies ( 16 ). Especially in geographic areas with limited stroke centers, PHPs can be reconceptualized as the backbone of the stroke survival chain in some low- and middle-income countries or regions ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Delays in any step can lead to delays in overall treatment and may even make the patient ineligible for certain reperfusion therapies ( 16 ). Especially in geographic areas with limited stroke centers, PHPs can be reconceptualized as the backbone of the stroke survival chain in some low- and middle-income countries or regions ( 16 , 17 ). In the present cross-sectional survey about assessment of stroke knowledge and awareness among PHPs from the KQI-ASC Project, we found that only 115 (39.7%) participants aware that the optimal time window for IVT in acute stroke is less than 4.5 h. Gender of PHPs, stroke management training received, and number of stroke management presentations given at local hospitals per year were the predictors of stroke knowledge and awareness among PHPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The health system requirements need to be specified for these patients, as do the competencies of health workers to care for them, and the clinical systems and routines to prioritize [ 32 , 33 ] for them to be quickly identified as critically ill and promptly treated —even when resources are limited such as at 3 am on a Sunday night [ 34 ]. Re-designing health services to have an increased focus on critical illness, in the same way as the longstanding focus on diagnoses with high mortalities [ 35 37 ], would target the highest risk patients and—as they are common—could be favorable for quality improvement, research, and innovation. Improving care of severely ill patients would benefit patients suffering from any underlying condition and have the advantage of improving care for patients lacking a definitive diagnosis, those with multimorbidity and those who have been mis-diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…The health system requirements need to be speci ed for these patients, as do the competencies of health workers to care for them, and the clinical systems and routines to prioritize [31,32] for them to be quickly identi ed as critically ill and promptly treated -even when resources are limited such as at 3am on a Sunday night [33]. Re-designing health services to have an increased focus on critical illness, in the same way as the longstanding focus on diagnoses with high mortalities [34][35][36], would target the highest risk patients and -as they are common -could be favorable for quality improvement, research, and innovation. Improving care of severely ill patients would bene t patients suffering from any underlying condition and have the advantage of improving care for patients lacking a de nitive diagnosis, those with multimorbidity and those who have been mis-diagnosed.…”
Section: The Prevalence Of Critical Illnessmentioning
confidence: 99%